Review of data on the dermal penetration of mineral oils and waxes used in cosmetic applications. (5th October 2017) - Petry, T.; Bury, D.; Fautz, R.; Hauser, M.; Huber, B.; Markowetz, A.; Mishra, S.; Rettinger, K.; Schuh, W.; Teichert, T.
Highlights: Upon dermal exposure, mineral oil and waxes are predominantly adsorbed to the stratum corneum. Only a minor fraction of mineral oil and waxes reach the deeper layer of the skin. There is no evidence that mineral oils or waxes as used in cosmetic applications are percutaneously absorbed. The cosmetic use of mineral oils and waxes does not present a risk to consumers due to lack of systemic exposure. Abstract: Mineral oils and waxes used in cosmetic products, also referred to as "personal care products" outside the European Union, are mixtures of predominantly saturated hydrocarbons consisting of straight-chain, branched and ring structures with carbon chain lengths greater than C16. They are used in skin and lip care cosmetic products due to their excellent skin tolerance as well as their high protecting and cleansing performance and broad viscosity options. Recently, concerns have been raised regarding potential adverse health effects of mineral oils and waxes from dermal application of cosmetics. In order to be able to assess the risk for the consumer the dermal penetration potential of these ingredients has to be evaluated. The scope and objective of this review are to identify and summarize publicly available literature on the dermal penetration of mineral oils and waxes as used in cosmetic products. For this purpose, a comprehensive literature search was conducted. A total of 13 in vivo (human, animal) and in vitro studies investigating the dermal penetration of mineral oils and waxes has been identified and analysed. The majority of the substances were dermally adsorbed to the stratum corneum and only a minor fraction reached deeper skin layers. Overall, there is no evidence from the various studies that mineral oils and waxes are percutaneously absorbed and become systemically available. Thus, given the absence of dermal uptake, mineral oils and waxes as used in cosmetic products do not present a risk to the health of the consumer.